2017
DOI: 10.1155/2017/7092521
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between Density and Mechanical Strength of Lightened Gypsums: Proposal for a Coefficient of Lightening

Abstract: This article develops a relationship between the reduction of density in lightened gypsum and the addition of expanded and/or extruded polystyrene waste from the construction sector and their mechanical behavior. The equations determined in this study allow us to know the flexural and compressive strengths of a lightened gypsum/plaster compound once its density is known. The results show that there is an exponential relationship between the density of the compound and its strength. The methodology followed inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The graph also shows the linear equation of the relationship between the density of the material and the flexural strength (Equation [3]). y = 0,0031 * density − 0,4465 [3] The results of this relationship between the two properties are compatible with those found by Santa Cruz Astorqui et al (28), where the authors concluded that there is an exponential relationship between the reduction of the composite density with the addition of EPS and its strength.…”
Section: Flexural and Compression Strength Analysissupporting
confidence: 86%
“…The graph also shows the linear equation of the relationship between the density of the material and the flexural strength (Equation [3]). y = 0,0031 * density − 0,4465 [3] The results of this relationship between the two properties are compatible with those found by Santa Cruz Astorqui et al (28), where the authors concluded that there is an exponential relationship between the reduction of the composite density with the addition of EPS and its strength.…”
Section: Flexural and Compression Strength Analysissupporting
confidence: 86%
“…In [23], a relationship was developed between the density reduction in clarified plaster and the addition of expanded polystyrene or extruded polystyrene residues from the construction sector, as well as the mechanical behavior of the additive (achieving compressive strength of 5.59 MPa). The purpose of this study was to investigate recycling, in addition to the fact that the production of calcium sulfate uses much less energy than the production of cements (70-90% less).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the amount of potassium polyacrylate present in the mixture, Figure 4 shows how the increase in the amount of this addition has an inverse effect on the improvement of the flexural and compressive strength of the material [19]. It should be noted that the incorporation of expanded perlite in the quantities used in this research has a positive effect on the improvement of the flexural strength of the new plaster material developed [12]. However, in general terms and because of the lower density of the plasters produced, the mechanical compressive strength is reduced with the incorporation of these lightening additions [23].…”
Section: First Experimental Phase Determination Of the Water/plaster ...mentioning
confidence: 93%
“…Extensive research has been conducted on the incorporation of additions in gypsum composite materials to improve some of their properties. Many studies focus on a reduction in the material's own weight [11] or the improvement of its thermal properties [12,13]. For instance, W. Luan et al successfully decreased the density of gypsum composites by incorporating pregelatinized starch, phosphates, dispersant compounds and synthetic fibers for the design of prefabricated panels [11].…”
Section: Introductionmentioning
confidence: 99%